Primary Brain Tumors in A Sample of Adult Iraqi Patients (Clinicopathological Study) (Iraqi Journal of Medical Sciences, 2024)
Background: Primary brain tumors are a diverse group of neoplasms. More than 120 histological types of these tumors have been classified by the World Health Organization (WHO). Brain tumors exhibit different behaviors according to age, histological type and location. In Iraq, few epidemiologic reports have highlighted the national and regional epidemiologic data regarding primary central nervous system (CNS) tumors.Objective: To identify the frequency of different histopathological types of primary brain tumors in samples of Iraqi patients, and to study the association with some clinicopathological parameters like age, gender, location and grade. Methods: A cross-sectional study including analysis of (200) patients who were presented with primary brain tumors. The samples are collected from Neurosurgery Teaching Hospital, Ghazi Al-Hariri Surgical Specialties Hospital and privet lab from January 2021 to January 2022.Results: The mean age was 42.94 years, ranging from (18 to 76) years, females were more than males as (55% and 45% respectively). Regarding anatomical location; supratentorial was 71% and infratentorial was 29%. With regard to histological types; diffuse glioma (43%) (from which glioblastoma most common subtype 59.3%) followed by meningioma (38%) (from which meningothelial meningioma represent 66.4). However, the ependymal tumors were only (3.5%). There was significant association between histological type and age (P = 0.005), and between histological type and grade (P = 0.001). However, there was no significant association between histological type and sex (P = 0.701).Conclusion: Diffuse glioma was the most common type that occur commonly in female and majority of cases situated in supratentorial region, also there was significant association between histological type with age and grade. Keywords: Adult tumors, glioma, histopathology, meningioma, primary brain tumorCitation: Hilal MS, Latif AH. Primary brain tumors in a sample of adult Iraqi patients (Clinicopathological study). Iraqi JMS. 2024; 22(1): 135-146. doi: 10.22578/IJMS.22.1.15
Keywords: Adult tumors; glioma; histopathology; meningioma; primary brain tumor